Social-Demographic Factors and Wage Determination - JIMOH ADAMS LUKMAN (Universitas Kuningan, 2022)
Most workers in Nigeria, like other developing nations, find it difficult to sustain themselves and their family despite the adjustment and re-adjustment of the minimum wage. This study, therefore, examined the effect of social-demographic factors such as: Age, Sex, Level of Education and Placements in an organization on wage determination. The study was a descriptive research survey. The population was all the 86 staff of the Federal Ministry of Labour and Productivity, Ilorin. While the study employed both stratified and simple random sampling technique. 60 employees of the ministry served as the study sample size. 66% of the respondents were males, while 34% female. The formulated hypothesis was tested with multiple regression. The result revealed that age, sex, level of education, family size and cadre level of placement of worker jointly predicted employee wage determination. The variable jointly predicted 17% changes observed in the reported employee wage determination. The study concluded that social-demographic factor such as: age, sex, level of education and employee placements in the organization affect wage determination. The study recommends that for an effective policy formulation the policymaker should consider the principle of wage differential because it ensure adequate coverage and measurement of the necessary variables that ought to be included while determining the minimum wage.